Clinical characterization of a novel RAB39B nonstop mutation in a family with ASD and severe ID causing RAB39B downregulation and study of a Rab39b knock down mouse model. Issue 9 (11th November 2021) - Mignogna, Maria Lidia; Ficarella, Romina; Gelmini, Susanna; Marzulli, Lucia; Ponzi, Emanuela; Gabellone, Alessandra; Peschechera, Antonia; Alessio, Massino; Margari, Lucia; Gentile, Mattia; D'Adamo, Patrizia
Abstract: Autism spectrum disorder (ASD) and intellectual disability (ID) often exist together in patients. The RAB39B gene has been reported to be mutated in ID patients with additional clinical features ranging from ASD, macrocephaly, seizures and/or early-onset parkinsonism. Here, we describe a novel RAB39B nonstop mutation [Xq28; c.640 T > C; p.( * 214Glnext * 21)] in a family with ASD, severe ID and poor motor coordination, and we assessed the pathogenicity of the mutation. A heterologous cell system and a Rab39b knockdown (KD) murine model, which mimic the nonstop mutation, were used to validate the deleterious effect of the RAB39B mutation. The mutation led to RAB39B protein instability, resulting in its increased degradation and consequent downregulation. Using a Rab39b KD mouse model, we demonstrated that the downregulation of RAB39B led to increased GluA2 lacking Ca 2+ -permeable AMPAR composition at the hippocampal neuronal surface and increased dendritic spine density that remained in an immature filopodia-like state. These phenotypes affected behavioural performance in a disease-specific manner. Rab39b KD mice revealed impaired social behaviour but intact social recognition. They also showed normal anxiety-like, exploratory and motivational behaviours but impaired working and associative memories. In conclusion, we found a novel RAB39B nonstop variant that segregated in a family with a clinical phenotype including ID, ASD and poor motor coordination. The pathogenicity of mutations causing the downregulation of RAB39B proteins, impacting AMPAR trafficking and dendritic spine morphogenesis, reinforced the idea that AMPAR modulation and dendritic spine assets could be considered hallmarks of neurodevelopmental disorders.